2015
DOI: 10.1016/bs.mie.2014.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Dependent Exponential Amplification of Self-Replicating RNA Enzymes

Abstract: A general analytical method for the detection of target ligands has been developed, based on a special class of self-replicating aptazymes. These “autocatalytic aptazymes” are generated by linking an aptamer domain to the catalytic domain of a self-replicating RNA enzyme. Ligand-dependent self-replication of RNA proceeds in a self-sustained manner, undergoing exponential amplification at a constant temperature without the assistance of any proteins or other biological materials. The rate of exponential amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…While not the focus of this paper, the aptamer has been used to create diagnostic tools through several approaches. Some of these approaches include electrochemical biosensors, fluorescent reporters, ,, surface plasmon resonance, fluorescence resonance energy transfer (FRET), and quartz crystal microbalances, , among others. In one interesting set of studies, Lam and Joyce fused the aptamer to cross-replicating RNA enzymes and demonstrated exponential growth of RNA enzymes in the presence of theophylline, but there was no activity when caffeine, theobromine, or trimethyl uric acid were present. Thus, the aptamer can be a powerful tool not only in cellular engineering, but also in detection and quantification of theophylline in biological and environmental samples.…”
Section: Applications Involving the Theophylline Aptamermentioning
confidence: 99%
“…While not the focus of this paper, the aptamer has been used to create diagnostic tools through several approaches. Some of these approaches include electrochemical biosensors, fluorescent reporters, ,, surface plasmon resonance, fluorescence resonance energy transfer (FRET), and quartz crystal microbalances, , among others. In one interesting set of studies, Lam and Joyce fused the aptamer to cross-replicating RNA enzymes and demonstrated exponential growth of RNA enzymes in the presence of theophylline, but there was no activity when caffeine, theobromine, or trimethyl uric acid were present. Thus, the aptamer can be a powerful tool not only in cellular engineering, but also in detection and quantification of theophylline in biological and environmental samples.…”
Section: Applications Involving the Theophylline Aptamermentioning
confidence: 99%